Biodegradable Natural Pectin‐Based Flexible Multilevel Resistive Switching Memory for Transient Electronics - Xu, Jiaqi; Zhao, Xiaoning; Wang, Zhongqiang; Xu, Haiyang; Hu, Junli; Ma, Jiangang; Liu, Yichun (Small (Weinheim an der Bergstrasse, Germany), 2019)
Transient electronics that can physically vanish in solution can offer opportunities to address the ecological challenges for dealing with the rapidly growing electronic waste. As one important component, it is desirable that memory devices combined with the transient feature can also be developed as secrecy information storage systems besides the above advantage. Resistive switching (RS) memory is one of the most promising technologies for next‐generation memory. Herein, the biocompatible pectin extracted from natural orange peel is introduced to fabricate RS memory devices (Ag/pectin/indium tin oxides (ITO)), which exhibit excellent RS characteristics, such as forming free characteristic, low operating voltages (≈1.1 V), fast switching speed (<70 ns), long retention time (>104 s), and multilevel RS behaviors. The device performance is not degraded after 104 bending cycles, which will be beneficial for flexible memory applications. Additionally, instead of using acid solution, the Ag/pectin/ITO memory device can be dissolved rapidly in deionized water within 10 min thanks to the good solubility arising from ionization of its carboxylic groups, which shows promising application for green electronics. The present biocompatible memory devices based on natural pectin suggest promising material candidates toward enabling high‐density secure information storage systems applications, flexible electronics, and green electronics. Biocompatible pectin extracted from natural orange peel is introduced to fabricate flexible multilevel resistive switching (RS) memory devices (Ag/pectin/indium tin oxides). The device exhibits excellent RS characteristics and it can be dissolved in deionized water rapidly thanks to the good solubility of pectin arising from ionization of its carboxylic groups.